Graphene growth and properties on metal substrates. (7th July 2015) - Dedkov, Yuriy; Voloshina, Elena
Abstract: Graphene–metal interface as one of the interesting graphene-based objects attracts much attention from both application and fundamental science points of view. This paper gives a timely review of the recent experimental works on the growth and the electronic properties of the graphene–metal interfaces. This work makes a link between huge amount of experimental and theoretical data allowing one to understand the influence of the metallic substrate on the electronic properties of a graphene overlayer and how its properties can be modified in a controllable way. The further directions of studies and applications of the graphene–metal interfaces are discussed.